Carfilzomib and Paclitaxel Co-Loaded Protein Nanoparticles an Effective Therapy Against Pancreatic Adenocarcinomas - Cheng WT; Ho HO; Lin SY; Liu DZ; Chen LC; Sheu MT (International Journal of Nanomedicine, 2021)
Wen-Ting Cheng,1,* Hsiu-O Ho,1,* Shyr-Yi Lin,2,3 Der-Zen Liu,4 Ling-Chun Chen,5 Ming-Thau Sheu1 1School of Pharmacy, College of Pharmacy, Taipei Medical University, Taipei, Taiwan, Republic of China; 2Division of Gastroenterology, Department of Internal Medicine, Wan Fang Hospital, Taipei Medical University, Taipei, Taiwan, Republic of China; 3Department of General Medicine, School of Medicine, College of Medicine, Taipei Medical University, Taipei, Taiwan, Republic of China; 4Graduate Institute of Biomedical Materials and Engineering, Taipei Medical University, Taipei, Taiwan, Republic of China; 5Department of Biotechnology and Pharmaceutical Technology, Yuanpei University of Medical Technology, Hsinchu, Taiwan, Republic of China*These authors contributed equally to this workCorrespondence: Ming-Thau SheuSchool of Pharmacy, College of Pharmacy, Taipei Medical University, 250 Wu-Hsing Street, Taipei, 11031, Taiwan, Republic of ChinaTel/Fax +886 2 2377 1942Email mingsheu@tmu.edu.twLing-Chun ChenDepartment of Biotechnology and Pharmaceutical Technology, Yuanpei University of Medical Technology, No. 306, Yuanpei Street, Hsinchu, 30015, Taiwan, Republic of ChinaTel/Fax +886 2 2377 1942Email d8801004@mail.ypu.edu.twPurpose: Therapeutic efficacy of pancreatic adenocarcinomas (PACs) with combined therapy of carfilzomib (CFZ) and paclitaxel (PTX) co-loaded in human serum albumin (HSA) nanoparticles (NPs) was examined.Methods: CFZ and PTX were encapsulated individually or combined into HSA NPs by a simple reverse self-assembly method developed to achieve an optimal combination ratio for synergistic therapy. CFZ or/and PTX loaded HSA nanoparticles were physically characterized and the evaluation of combination index, drug release, pharmacokinetic, anti-tumor, and biodistribution studies were conducted.Results: All resultant drug-loaded HSA NPs were spherical with a particle size of < 150 nm and a zeta potential of − 21.1∼− 23.0 mV. Drug loading rates and entrapment efficiencies were 9.1%∼ 10.1% and 90.7%∼ 97.1%, respectively. CFZ and PTX demonstrated synergistic effects in an MIA PaCa-2 cytotoxicity at a 1:2 ratio (CI50 were 0.01∼ 0.25). In vitro dissolution revealed that the CFZ/PTX ratio released from the co-loaded HSA NPs (CFZ/PTX/HSA NPs) was about 1.77∼ 2.08, which conformed to the designated loaded ratio. In vivo evaluation showed that the combined therapy of CFZ and PTX at a 1:2 ratio co-loaded in HSA NPs (CFZ/PTX/HSA NPs) demonstrated optimal synergistic improvement of the growth inhibition of MIA PaCa-2 cells with less systematic toxicity, even though the pharmacokinetic profiles observed did not show obvious beneficial and their biodistributions in tumors were found to be smaller.Conclusion: The one-pot reverse assembly method developed was environmentally friendly and capable of co-loading an optimal combination ratio of two chemodrugs into HSA NPs for synergistic therapy.Keywords: human serum albumin, nanoparticles, carfilzomib, paclitaxel, co-loading, synergism